Monitoring program for mammals in a protected area of Colombia - Jiménez, Germán; Ecology and Systematics Unit (UNESIS), Department of Biology, Pontificia Universidad Javeriana, Bogotá Colombia & Centre for Research and Studies on Biodiversity and Genetic Resources (CIEBREG), Pereira, Colombia. Wildlife Conservation and Management Group, Pontificia Universidad Javeriana, Bogotá, Colombia. (2017)
Between the second semester of 2009 and the first semester of 2011, camera traps were set up in conserved and disturbed habitats in the Otún Quimbaya Flora and Fauna Sanctuary. From a sampling effort of 2,066 camera-days, 673 photographs of 157 independent events were obtained for eight species of wild mammals and a domestic one. Their activity patterns were mainly nocturnal even for those species reported as diurnal. The impact of human interference and exotic species was evident for two species: Tapirus pinchaque and Cerdocyon thous. The former was observed below its altitudinal range with activity patterns mainly crepuscular and nocturnal. The second was observed in the same habitats where domestic dogs were found, with activity patterns mainly crepuscular and nocturnal. These findings suggest that both species have altered their activity patterns. Actions must be focused on decreasing the interaction of these mammals with humans and domestic dogs.